Pengembangan Aplikasi Mobile Pengaduan Layanan dan Maintenance Berbasis Android pada Fakultas Ilmu Komputer Universitas Brawijaya - Hanoum Eva Hayati; Denny Sagita Rusdianto; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Faculty of Computer Science, Brawijaya University (FILKOM) has public and equipment affair sub section, which is responsible for handling complaints and maintenance services at FILKOM. In handling these responsibilities, public and equipment affair sub section have difficulties due to a mechanism that has not run optimally. This resulted in complaints come from various sources so that it could not be recorded properly and complainants often complained about the handling of complaints that had been reported. In handling maintenance, the data collection history of an inventory is still not maximal. In order for the implementation of these functions to run optimally, a container for complaint complaints and maintenance scheduling is needed. One solution is develop an Android-based service complaint and maintenance (PLM) application. This development starts with requirement engineering that makes 18 functional and 2 non-functional requirement and 3 actor roles. In development process, the PLM application applies the waterfall method because the requirements have been defined as a whole at the beginning. The design process is done by object-oriented modeling and program implementation using java language on Android Studio and implementing data using Firebase. Based on the testing, the results obtained 100% for unit testing, validation, and compatibility and obtained usability testing with value of 100% for the task scenario and 97.2% for the USE questionnaire method.